LEARNING CHEMISTRY WITH THE HIERARCHY MODE OFELECTRONIC CONCEPT MAPPING STRATEGY - ABANIKANNDA, Mutahir (Universitas Negeri Semarang, 2024)
An electronic hierarchy concept mapping instructional package has been designed, developed and validated, to be employed as a learning strategy for learning chemistry. This study assesses the attitude of students exposed to the strategy. Design-based research was employed using the mixed-method approach divided into two stages. In the first stage, the design and development of the package were carried out, qualitative and quantitative expert validation was done thereafter. The second stage involved the assessment of the developed package by assessing students’ attitudes to the package. Experts’ judgments revealed that the developed package meets up with the required standard of instructional design and development and is suitable for learning. The findings in this study also showed that the use of the strategy elicited a highly positive attitude from students. It can be concluded therefore, those electronic hierarchy concept mapping strategies are better innovative approaches to learning chemistry in Nigerian schools.